2016
DOI: 10.1002/clen.201500501
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Triton X‐100 in Water Falling Film Dielectric Barrier Discharge Reactor

Abstract: The aim of this study was to investigate the degradation of the non‐ionic surfactant Triton X‐100 (TX‐100) by using an advanced oxidation process in a non‐thermal plasma reactor based on water falling film dielectric barrier discharge (DBD). The effects of two catalytic plasma systems, Fe2+/DBD and H2O2/DBD, were tested to improve the degradation of TX‐100 and the mineralization efficiency in the DBD reactor. Both catalytic systems exhibited significant improvements in degradation efficiency, especially in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…There is only limited data on the degradation of Triton X-100 using atmospheric plasma in the literature. Aonyas et al, (2016) have reported the efficient degradation of Triton X-100 (at 100 mg/L initial concentration) in a falling film DBD reactor operating at an input power of 180 W. Their estimated G50 and EE/O values of 1167 mg/kWh and 75 kWh/m 3 , respectively (Aonyas et al, 2016) are however not as efficient as those found in the present study despite the fact that we used a 4-fold lower Triton X-100 initial concentration than theirs. Triton surfactants of different chain length, namely Triton X-45 (n = 4.5) and Triton X-405 (n = 35), were investigated in another study using miniaturized atmospheric pressure glow discharges generated in contact with small sized flowing liquid cathode systems (Jamróz et al, 2014).…”
Section: Resultscontrasting
confidence: 80%
“…There is only limited data on the degradation of Triton X-100 using atmospheric plasma in the literature. Aonyas et al, (2016) have reported the efficient degradation of Triton X-100 (at 100 mg/L initial concentration) in a falling film DBD reactor operating at an input power of 180 W. Their estimated G50 and EE/O values of 1167 mg/kWh and 75 kWh/m 3 , respectively (Aonyas et al, 2016) are however not as efficient as those found in the present study despite the fact that we used a 4-fold lower Triton X-100 initial concentration than theirs. Triton surfactants of different chain length, namely Triton X-45 (n = 4.5) and Triton X-405 (n = 35), were investigated in another study using miniaturized atmospheric pressure glow discharges generated in contact with small sized flowing liquid cathode systems (Jamróz et al, 2014).…”
Section: Resultscontrasting
confidence: 80%
“…salina organisms are mostly used for toxicity tests of extremely toxic substances, for example, drugs used as cytostatics [49]. This toxicological test has been applied to the assessment of the ecotoxicological status of non-thermal plasma treated water polluted by reactive textile dyes [16,50], herbicides [32,51], surfactants [38,52], 4-chlorophenol [48], and ibuprofen [53]. In the present study, the A. salina toxicity test was performed for untreated nicotine solutions and for nicotine solutions treated with different DBD systems.…”
Section: Results Of Toxicity Bioassaymentioning
confidence: 99%
“…The addition of Fe 2+ was used to increase the oxidation power of the plasma, since Fe 2+ will participate in the reaction with generated H 2 O 2 [36]. This reaction is also known as the Fenton reaction in which • OH is generated by the following equation (3) [37][38][39]:…”
Section: Degradation Efficiency Of Nicotine Using Different Dbd Treat...mentioning
confidence: 99%
“…In other words, the application of potential to the photoactive layers allows for the irradiation time to be significantly reduced in the presence of hierarchical photoactive materials composed of tungsten oxide and hematite. It is noteworthy that the proposed hierarchical photoactive system exhibited higher photodegradation efficiency and lower decomposition time (after 30 min under a bias voltage) in comparison with that of the other reported systems [62][63][64]. For instance, the mineralization rate of Triton TM X-114 reached up to 26% using TiO2 under UV irradiation after 120 min, but with an additional oxidizing reagent (hydrogen peroxide), the degradation rate achieved 67% after 120 min [63].…”
Section: Spectrophotometric Analysismentioning
confidence: 77%